Technology enhanced learning (TEL) of Karnaugh map (K-Map) - Nadya, Kezia (2017)
Karnaugh Map (K-Map) is one of the common and fundamental techniques used for digital logic minimization in digital electronic circuit design and it is usually learnt in a lower year undergraduate course of a University programme in Electronic Engineering. In this project, a Technology-Enhanced Learning (TEL) software program of K-Map was developed to help create better learning curve and to promote students’ interest in Digital Electronics. Specifically, the project is to develop a software program that generates Boolean functions for users to practice the K-map technique for logic minimization. The program will generate a logic function, work out its minimized solution and check the user’s input answer. It provides a GUI (Graphic User Interface) that serves as a K-Map Practice Platform on which users can generate logic functions of up to 4 variables and with or without don’t care terms. The minimized expression can be in either Sum of Product (SOP) or Product of Sum (POS) form. It also lists all the Prime Implicants (PIs) and Essential Prime Implicants (EPIs) and displays all possible solutions if there are more than one minimized solutions. Additionally, the generated logic functions and the minimized solutions can be saved to text files and imported to external system such as OASIS for practice and assessment test. Technically, the program was developed in the Microsoft Visual Studio Platform with Visual Basic as the programming language. Quine McClukey tabular method is implemented to perform the Boolean logic minimization. The method is applied to find all the prime implicants and identify the essential prime implicants of the Boolean functions. Subsequently, Petrick’s method is used to detect all the possible and most simplified solutions. Hence, the program is able to find all the possible minimized solutions for logic functions of up to 4 variables and with or without don’t care terms. This report documents the design, development and implementation of the TEL software program. Quine McClukey method and Petrick’s method are reviewed and their implementations are detailed. The development of the GUI is described and test examples and test results are presented and discussed.